2010
DOI: 10.1007/s11117-009-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Martingales in Banach lattices, II

Abstract: This note is a follow-up to Troitsky (Positivity 9(3): [437][438][439][440][441][442][443][444][445][446][447][448][449][450][451][452][453][454][455][456] 2005). We provide several sufficient conditions for the space M of bounded martingale on a Banach lattice F to be a Banach lattice itself. We also present examples in which M is not a Banach lattice. It is shown that if F is a KB-space and the filtration is dense then F is a projection band in M. IntroductionThis short note is a follow-up to [5], where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In [6] and [2] several sufficient conditions are established where the set of bounded martingales M is a Banach lattice. In [2], counter examples are provided where M is not a Banach lattice. So, one may similarly ask when are M X and M E Banach spaces and Banach lattices?…”
Section: Propositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [6] and [2] several sufficient conditions are established where the set of bounded martingales M is a Banach lattice. In [2], counter examples are provided where M is not a Banach lattice. So, one may similarly ask when are M X and M E Banach spaces and Banach lattices?…”
Section: Propositionmentioning
confidence: 99%
“…Moreover, under certain conditions on the Banach lattice, it was shown that the set of bounded martingales forms a Banach lattice with respect to the point-wise order. In 2011, H. Gessesse and V. Troitsky [2] produced several sufficient conditions for the space of bounded martingales on a Banach lattice to be a Banach lattice itself. They also provided examples showing that the space of bounded martingales is not necessarily a vector lattice.…”
Section: Introductionmentioning
confidence: 99%
“…However, we will present a counterexample to the contrary. Our example will be based on [8,Example 6], which we outline here for convenience of the reader.…”
Section: Krickeberg's Formulamentioning
confidence: 99%
“…We denote with M = M F, (E n ) the space of all martingales on F with respect to the filtration (E n ). The space M equipped with the coordinate-wise order is an ordered vector space and we denote with M + the positive cone of M. There is an extensive literature on abstract martingales on vector and Banach lattices, see, e.g., [5,18,11,15,10,12,8,9,6,7]. For unexplained terminology on ordered vector and Banach spaces we refer the reader to [2,3,13].…”
mentioning
confidence: 99%
“…We now prove (5)⇒(1). Assume (5) We apply this result to establish the following dual version of [4,Theorem 4.3]. Recall that a net (x α ) in a vector lattice X is unbounded order Cauchy (or uo-Cauchy, for short), if the net (x α − x α ′ ) (α,α ′ ) uo-converges to 0 in X. Theorem 2.2.…”
Section: When Does Uo-convergence Imply W * -Convergence?mentioning
confidence: 99%